Cortical tension regulates desmosomal morphogenesis - Moch, Marcin; Schieren, Jana; Leube, Rudolf E. (Frontiers in Cell and Developmental Biology, 2022)
Mechanical stability is a fundamental and essential property of epithelial cell sheets. It is in large part determined by cell-cell adhesion sites that are tightly integrated by the cortical cytoskeleton. An intimate crosstalk between the adherens junction-associated contractile actomyosin system and the desmosome-anchored keratin intermediate filament system is decisive for dynamic regulation of epithelial mechanics. A major question in the field is whether and in which way mechanical stress affects junctional plasticity. This is especially true for the desmosome-keratin scaffold whose role in force-sensing is virtually unknown. To examine this question, we inactivated the actomyosin system in human keratinocytes (HaCaT) and canine kidney cells (MDCK) and monitored changes in desmosomal protein turnover. Partial inhibition of myosin II by para-nitro-blebbistatin led to a decrease of the cells' elastic modulus and to reduced desmosomal protein turnover in regions where nascent desmosomes are formed and, to a lower degree, in regions where larger, more mature desmosomes are present. Interestingly, desmosomal proteins are affected differently: a significant decrease in turnover was observed for the desmosomal plaque protein desmoplakin I (DspI), which links keratin filaments to the desmosomal core, and the transmembrane cadherin desmoglein 2 (Dsg2). On the other hand, the turnover of another type of desmosomal cadherin, desmocollin 2 (Dsc2), was not significantly altered under the tested conditions. Similarly, the turnover of the adherens junction-associated E-cadherin was not affected by the low doses of para-nitro-blebbistatin. Inhibition of actin polymerization by low dose latrunculin B treatment and of ROCK-driven actomyosin contractility by Y-27632 treatment also induced a significant decrease in desmosomal DspI turnover. Taken together, we conclude that changes in the cortical force balance affect desmosome formation and growth. Furthermore, they differentially modulate desmosomal protein turnover resulting in changes of desmosome composition. We take the observations as evidence for a hitherto unknown desmosomal mechanosensing and mechanoresponse pathway responding to an altered force balance.